Current practice in the Histology practical classes of Anatomy inthe undergraduate medical education in 15 Bangladesh (Bangladesh Journal of Medical Education, 2017)
Background: Histology in the broader sense is devoted to the study of the micro anatomical structure of cells, tissues and organ systems. One of the major areas of laboratory teaching in the medical curriculum is Histology. This study aimed to assess the current practice of teaching learning in Histology practical classes of Anatomy in undergraduate medical education in Bangladesh.Methods: This descriptive type of cross sectional study was carried out in ten (four government and six non-government) medical colleges from January 2014 to December 2014. Direct observation of 30 Histology practical classes were made by the researcher herself. Different aspects of the classes were scored following a structured checklist by using a four point rubric.Results: The study findings revealed that the status of the 'light' of the classroom required very minimal efforts for attaining a good standard. On the other hand, observations revealed that considerable efforts are needed to reach a good standard towards 'grouping' of the students in the class and making proper 'conclusion' of the teaching session. Regarding the rest of the issues, it was found that only some or moderate efforts are required for getting to such standards.Conclusions: The common barriers found in this study were lack of training of teachers, large number of students and inadequacy of modernized teaching-learning aids. So in order to increase the effectivity of the practical classes modern techniques should be practiced. In addition teachers should be equipped with adequate knowledge on teaching pedagogies through frequent training and orientation programme in laboratory teaching.Bangladesh Journal of Medical Education Vol.5(1) 2014: 15-19